Os espaços e equipamentos públicos de lazer da cidade de Araguaína (TO) sob a ótica de seus moradores - Elisabeth Sydow (2017)
Besides being a legal right, leisure equipment and areas are favorable to social interaction, motor, emotional, and intellectual development promoting life quality for citizens of all ages. But, for that, there need to be enough leisure equipment and areas, in good condition, and equal access opportunities for everyone to enjoy them. Two studies were developed in this thesis. The first study aimed to identify and characterize the public leisure equipment and areas in the town of Araguaína and their access and use condition. Its delineation was descriptive-exploratory. The second study aimed to access the perception of the residents about leisure in their free time and the use of public leisure areas available in the municipality. The data collection was performed through the application of a questionnaire to 241 university students. The answers were analyzed qualitatively and quantitatively, based on the Content Analysis and it was performed simple descriptive statistics, frequency count, and variable association tests. The results show that the offer of public leisure equipment and areas to the population of Araguaína is insufficient in terms of quality, quantity, and access. The inhabitants understanding of free time is that of time with no obligations and of time for leisure practices. Their leisures practices are related to physical activities, going to farms, and strolling. Parque Cimba and the squares are among the most attended public leisure areas. The inhabitants would like the town to offer cultural activities and areas such as theaters, museums, bookshops, libraries, musical and cultural events. The inhabitants suggestion, regarding the available leisure areas, is that it is necessary to improve their use condition, that there is more security, and that more leisure areas are available to the community.